Design and Implementation of the BAZNAS Microfinance Desa Application for Empowering Mustahiq Micro Enterprises - Muhammad Romadhona Kusuma; Noor Azis (Journal of Innovation and Computer Science, 2025)
Microfinance has become an important strategy for expanding financial access to micro-entrepreneurs, who dominate the Indonesian economic structure. Since 2018, the National Zakat Agency (BAZNAS) has introduced the BAZNAS Microfinance Desa (BMD) program, which is based on zakat, infaq, and alms funds. This research aims to design and implement a BMD digital application to manage sharia financing based on al-Qardhul Hasan and productive grants, while also supporting transparent monitoring and reporting. The research method employs a Design Science Research (DSR) approach, involving the stages of problem identification, artifact design, application implementation, and program evaluation across several regional BMDs. The application supports the financing application process, Mustahiq eligibility assessment, fund disbursement, repayment recording, and a centralized reporting dashboard. The implementation results show that the BMD application can improve the efficiency of administrative processes, reduce the risk of non-performing financing, and accelerate the consolidation of Mustahiq data at the national level. This research contributes to the development of a more transparent, measurable, and sustainable zakat-based microfinance model. It is relevant to the national zakat digitalization agenda and the achievement of the Sustainable Development Goals (SDGs).